Green, fast and simple dispersive liquid-liquid microextraction method by using hydrophobic deep eutectic solvent for analysis of folic acid in fortified flour samples before liquid chromatography determination. (1st August 2020) - Faraji, Mohammad; Mahmoodi-Maymand, Masoumeh; Dastmalchi, Farnaz
Highlights: A hydrophobic green deep eutectic solvent (DES) was synthesized and used in DLLME. Application of hydrophobic DES leads to omit emulsifier solvent. Application of DES leads to omit ion-pairing reagent in folic acid extraction. The method is sensitive, fast, reliable, inexpensive and green. The applicability of the procedure is evaluated with wheat flour samples. Abstract: A fast, simple, sensitive, and efficient vortex-assisted dispersive liquid-liquid microextraction method (VA-DES-DLME) was developed based on hydrophobic deep eutectic solvent for extraction of folic acid from flour samples followed by HPLC determination. Hydrophobic DES was prepared by mixing amylalcohol as a hydrogen bond donor and methyltriocthylammonium chloride as a hydrogen bond acceptor. Factors affecting DLLME were considered and optimized. In optimal conditions, the calibration curve was linear in the range 5.0–500 ng g −1 with a correlation coefficient higher than 0.99. The limit of detection (LOD) and the limit of quantification (LOQ) were 1.0 and 3.0 ng g −1, respectively. The intra-day and inter-day precision at concentrations of 10 and 100 ng g −1 were less than 8%. Finally, application of the proposed procedure was investigated by folic acid analysis in flour samples and the relative recoveries obtained were acceptable (Recovery ≥ 90%).